rDNA loci and heterochromatin positions support a distinct genome type for 'x=9 species' of section Arachis (Arachis, Leguminosae) - Silvestri, María Celeste (2014)
Most species of the genus Arachis (Leguminosae; 80 spp.) are diploid with x=10 and only four species have x=9 chromosomes. Three of these x=9 species belong to section Arachis and are morphologically and chromosomally similar. To study the homeology of the genomes of x=9 species and their relation to other genomes in section Arachis we applied fluorescence in situ hybridization (FISH) of 18S-26S and 5S rDNA and 4´, 6-diamidino-2-phenylindole (DAPI) banding. FISH revealed for these three species one pair of 5S rDNA sites interstitially within the short arm of the metacentric pair 6 and one pair of 18S-26S rDNA sites in the proximal region of the long arm of the SAT chromosomes. Conspicuous DAPI+ bands were detected pericentromerically in all nine chromosome pairs of A. decora and A. praecox and in all but one pair of A. palustris. Our results suggest that all three species with x=9 of section Arachis share the same genome type and are different from the other genome types A, B, D, F, and K described for this section. Apparently, the x=9 species of section Arachis form a monophyletic group characterized by a genome type that we propose to call G genome.